2004
DOI: 10.1111/j.1462-8902.2004.00352.x
|View full text |Cite
|
Sign up to set email alerts
|

Lipids and lipoprotein(a) concentrations in Pakistani patients with type 2 diabetes mellitus

Abstract: The present study led us to conclude that serum Lp(a) levels are significantly raised in type 2 DM and have a positive correlation with serum total and LDL-c levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
36
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 34 publications
6
36
1
Order By: Relevance
“…This complements other recent studies [37][38][39][40]. The association between type 2 diabetes mellitus and obesity is probably the result of multiple mechanisms, including rises in plasma free fatty acids and tumor necrosis factor alpha released from "full" adipocytes [41].…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…This complements other recent studies [37][38][39][40]. The association between type 2 diabetes mellitus and obesity is probably the result of multiple mechanisms, including rises in plasma free fatty acids and tumor necrosis factor alpha released from "full" adipocytes [41].…”
Section: Discussionsupporting
confidence: 69%
“…The association between type 2 diabetes mellitus and obesity is probably the result of multiple mechanisms, including rises in plasma free fatty acids and tumor necrosis factor alpha released from "full" adipocytes [41]. More recently, it has been shown that in the Indian population, general and central obesity was associated with a family history of diabetes [39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SSRI: Serotonin reuptake inhibitors, SNRI: Serotonin noradrenaline reuptake inhibitors, TCA: Tricyclic antidepressants, AED: Antiepileptic drugs, GABA: Gamma amino butyric acid It has been found that apoA-I production rates are higher among women leading to higher amount of HDL than men. [20] Females had significantly higher incidence of depression as compared to males. Twin Swedish study indicated that liability to major depression among female is largely genetic in origin.…”
Section: Discussionmentioning
confidence: 99%
“…Lipoprotein(a) blood plasma concentrations are elevated in patients with type 2 diabetes (20,21). Such elevation results in an enhanced risk of atherosclerosis (22,23).…”
Section: Introductionmentioning
confidence: 99%